Pengaruh Kualitas Produk dan Harga Terhadap Minat Beli Beras Selancar (Studi Kasus pada Ibu Rumah Tangga di Kota Baru Jalan Kapten Satar RT.10 RW.03 Kecamatan Lahat) - Darwin Kesuma (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2020)
The Effect of Product Quality and Price on Purchase Intention for Selancar Rice (Case Study on Housewives in Kota Baru Jalan Kapten Satar RT. 10 RW. 03 Lahat). This research was conducted on housewives located at Jalan Kapten Satar RT 10 RW 03 No. 25 Kelurahan Kota Baru, Lahat District. The research objective was to see the effect of the product and price on buying interest in surfing rice. The regression equation Y = 10.588 + 0.453 X1 + 0.339 X2 + e. Based on statistical data analysis, the indicators in this study are valid and reliable. The individual order of each variable with the most influence is the product quality variable with a regression coefficient of 0.453 then the price variable with a regression coefficient of 0.339. Obtained t count variable product quality (X1) of 2.658> 2.011 and variable price (X2) obtained at 2.905> 2.011. This means that t is greater than t table, then H_0 is rejected and H1 is accepted. Obtained an F calculated value of 7.009> 3.20 so that it can be ignored that there is a simultaneous (joint) influence between product quality (X1) and price (X2) on buying interest (Y) of surfing rice. Analysis of the coefficient of determination of 23% means that there is a very weak relationship between the independent variables and the related variables and the rest is 77%. By other factors that are not discussed in this study.